Modeling and calculation of acoustic radiation of underwater stiffened cylindrical shells treated with local damping - Zou, Ming-Song; Tang, Huai-Cheng; Liu, Shu-Xiao (Marine structures, 2023)
Damping materials are widely used and playing an essential role in reducing the vibration and noise of various ships and underwater vehicles. In practical engineering, damping materials are often applied over the structural surface of ships and underwater vehicles. They are generally distributed not evenly in the whole area, but locally in some vital regions. The stiffened cylindrical shell is the most representative configuration for the main structure of underwater vehicles. Therefore, research on modeling and calculation of underwater acoustic radiation from stiffened cylindrical shells locally treated with damping has high practical value. This paper introduces a mixed analytical-numerical acoustic-vibration interaction method to achieve efficient calculation of the vibration and acoustic radiation from a locally damped cylindrical shell immersed in water. Two kinds of vibration and noise reduction measures are proposed for the damping treatment of a large-scale stiffened cylindrical shell structure. Calculation and analysis are carried out for both measures. The results can provide reference for developing the technology of reducing vibration and noise from ships and underwater vehicles via damping treatment. •This paper introduces a mixed analytical-numerical acoustic-vibration interaction method. Vibration and acoustic radiation from a locally damped cylindrical shell immersed in water is efficiently calculated.•This method has the advantages of simple modeling and a small computation.•Based on this method, two noise reduction measures for local damping treatment are proposed and analyzed.